Hubungan Karakteristik Pasien dan Aktivitas Fisik dengan Kejadian Osteoarthritis Pada Lansia di RSU Sri Pamela Tebing Tinggi Tahun 2025 - Sinuraya, Noor Azizah Shahifa; Hiswani, Hiswani (Innovative: Journal Of Social Science Research, 2025)
This study aimed to analyze the association between patient characteristics and physical activity with the incidence of OA. This research applied an analytic observational method with a cross-sectional design. This research had a total of 101 respondents were selected using purposive sampling. The results showed a statistically significant association (p value < 0,05) between variable age, sex, family history, history of joint trauma, body mass index (BMI), and physical activity with OA. Meanwhile, there was no significant association (p value > 0,05) between occupational with OA. It is recommended that individuals with a history of joint trauma receive appropriate and timely treatment to prevent the progression of OA. In addition, healthcare institutions are advised to strengthen inter-department collaboration and promote public education, especially among pre-elderly individuals, regarding the importance of regular physical activity and maintaining an ideal body weight.